Benthic foraminiferal I/Ca, fish teeth Ce anomaly, and Mn enrichment factor of bulk sediment during the late Paleocene-early Eocene - Xiaoli Zhou; Ellen Thomas; Arne M E Winguth; Andy Ridgwell; Howie D Scher; Babette A A Hoogakker; Rosalind E M Rickaby; Zunli Lu (PANGAEA, 2016)
Important insight into the relationship between de-oxygenation and warming can be obtained from the geological record, but evidence is limited because few ocean oxygenation records are available for past greenhouse climate conditions. We use I/Ca in benthic foraminifera to reconstruct late Paleocene through early Eocene bottom and pore-water redox conditions in the South Atlantic and Southern Indian Oceans, and compare our results with those derived from Mn speciation and the Ce anomaly in fish teeth.
Supplement to: Zhou, X et al. (2016): Expanded oxygen minimum zones during the late Paleocene-early Eocene: Hints from multiproxy comparison and ocean modeling. Paleoceanography, https://doi.org/10.1002/2016PA003020